Blood donors and non-donors profile in a city in the south of Brazil - Belato, Débora (2011)
This study delineated the profile of blood donors and non-donors of a city in the South of Brazil. It is a cross-sectional study, with quantitative approach. Data was collected through forms filled out by a sample of 236 undergraduate students and 152 people that had access to the Emergency Room of the hospital of the same city, totalizing 388 individuals. The form was filled out during October of 2008, and data obtained consisted of: gender, level of schooling, age and whether or not they were blood donors. Moreover, the reasons to donate or not donate blood were questioned. The number of women and men who are donors is similar. Concerning age, young adults predominate when it comes to blood donation. The most frequent reason to donate was the feeling of helping people and the most frequent reason not to donate was the fear of the procedure. The results point out the need for further clarification about the process of blood donation.